(untitled) (Semiárida, 2018)
This article reports the recording of Limnobium laevigatum (Hydrocharitaceae) for the first time ever in the province of La Pampa, Argentina. Specimens were collected from a surface rainwater drain of Ingeniero Luiggi town, and their presence gave way to a taxonomic novelty at the level of species, genus and family for the provincial flora. DOI: http://dx.doi.org/10.19137/semiarida.2016(01).25-27